Manajemen Hybrid Learning Politeknik Ilmu Pelayaran Semarang - Darul Prayogo; Supendi, Supendi; Antoro, Dwi; Huda, Samsul; Fitrianingsih, Ariyanti; Surjaman, Febria; Purwantono, Purwantono; M. Choeroni, M. Choeroni; Sugiyarto, Sugiyarto (Media Manajemen Pendidikan, 2024)
The COVID-19 pandemic has changed human behavior, including education. Politeknik Ilmu Pelayaran Semarang is one of those who feel the impact of the pandemic. Adjustments to education management are made to improve and ensure learning can occur properly. Online learning is not new, but the pandemic has made digital learning directly used as a solution to overcome this. Using a case study approach, this paper presents our experience in organizing online education at the Politeknik Ilmu Pelayaran Semarang. The results showed that although online learning can be used in teaching and learning activities during the pandemic, it has not been able to replace practical learning. As the COVID-19 pandemic declines in Indonesia, the author wants to create one that can contribute to learning in the future. Using learning recordings with simulators, practicum recordings, and theoretical learning recordings is expected to help to learn.